Exercise to preserve β‐cell function in recent‐onset Type 1 diabetes mellitus (EXTOD) – a randomized controlled pilot trial. Issue 11 (14th September 2017) - Narendran, P.; Jackson, N.; Daley, A.; Thompson, D.; Stokes, K.; Greenfield, S.; Charlton, M.; Curran, M.; Solomon, T. P. J.; Nouwen, A.; Lee, S. I.; Cooper, A. R.; et al.
Abstract: Aim: Residual β‐cell function is present at the time of diagnosis with Type 1 diabetes. Preserving this β‐cell function reduces complications. We hypothesized that exercise preserves β‐cell function in Type 1 diabetes and undertook a pilot trial to address the key uncertainties in designing a definitive trial to test this hypothesis. Methods: A randomized controlled pilot trial in adults aged 16–60 years diagnosed with Type 1 diabetes within the previous 3 months was undertaken. Participants were assigned to control (usual care) or intervention (exercise consultation every month), in a 1 : 1 ratio for 12 months. The primary outcomes were recruitment rate, drop out, exercise adherence [weeks with ≥ 150 min of self‐reported moderate to vigorous physical activity (MVPA)], and exercise uptake in the control group. The secondary outcomes were differences in insulin sensitivity and rate of loss of β‐cell function between intervention and control at 6 and 12 months. Results: Of 507 individuals who were approached, 58 (28 control, 30 intervention) entered the study and 41 completed it. Participants were largely white European males, BMI 24.8 ± 3.8 kg/m 2, HbA1c 75 ± 25 mmol/mol (9 ± 2%). Mean level of objectively measured MVPA increased in the intervention group (mean 243 to 273 min/week) and 61% of intervention participants reached the target of ≥ 150 min/week of self‐reported MVPA on at least 42 weeks of the year. Physical activity levels fell slightly in the control group (mean 277 to 235 min of MVPA/week). There was exploratory evidence that intervention group became more insulin sensitive and required less insulin. However, the rate of loss of β‐cell function appeared similar between the groups, although the change in insulin sensitivity may have affected this. Conclusion: We show that it is possible to recruit and randomize people with newly diagnosed Type 1 diabetes to a trial of an exercise intervention, and increase and maintain their exercise levels for 12 months. Future trials need to incorporate measures of greater adherence to exercise training targets, and include more appropriate measures of β‐cell function. (Clinical Trials Registry No; ISRCTN91388505) What's new?: We show that it is possible to recruit and randomize people with newly diagnosed Type 1 diabetes to a trial of an exercise intervention, and increase and maintain their exercise levels over 1 year. Our findings contradict the only other study in Type 1 diabetes adults, which did not show an increase in exercise levels. We also show that an exercise programme is safe and can be undertaken without hypoglycaemia or injury, and appears to improve physical fitness and insulin sensitivity, and reduce insulin requirements. We objectively measure physical activity in people with newly diagnosed Type 1 diabetes and show them to undertake more physical activity than previously reported. In the setting of a pilot feasibility trial, the rate of loss of β‐cell function does not appear to be influenced by exercise. However, the increased insulin sensitivity associated with exercise may influence the validity of meal‐stimulated increases in plasma C‐peptide concentration as a measure of residual β‐cell function.